Influence of Long-Term Storage Conditions on Lithium Metal Anode Surface in Liquid Carbonate-Based Electrolyte. Issue 8 (1st August 2022) - Seara, Josu; Alcaide, Francisco; Barrio, Victoria Laura; Benayad, Anass; Ayerbe, Elixabete
Abstract : Lithium metal electrodes have been submitted to a long-term storage in contact with carbonated-based electrolyte at different temperatures, with the aim of gaining more understanding on the impact of aging conditions on the lithium metal surface. To do so, the evolution of lithium surface∣electrolyte interface has been monitored via electrochemical impedance spectroscopy, X-ray photoelectron spectroscopy and FE-SEM techniques, to correlate the change of the interface properties with the chemical and morphological modifications at the electrode's surface. After this aging, lithium electrodes were galvanostatically cycled in symmetric Li∣Li coin cell configuration at 10, 25 and 45 °C. Through this approach, a better cycling stability was observed in those cells stored at 45 °C, which can be ascribed to the more compact lithium electrodeposition than that observed in the rest of cells previously aged at lower temperatures. These results indicate that calendar at high temperature condition benefits lithium electrode performance, which can be attributed to a homogeneous passivation of the metal surface with fluorine and/or phosphate-based compounds, following XPS measurements, which can improve the behaviour of the solid electrolyte interface.